Effect of depression among taekwondo students and its relationship with negative events due to COVID-19 - Mohammadbagher Forghani Ozrudi; Somayeh Faghanpour; Roghayeh Gholampour Goli; Leonid Podrigalo (Physical Education of Students)
Background and Study Aim. The aim of this research was to examine The effect of depression among taekwondo students and its relationship with negative events due to COVID-19 in Mazandaran University.